Haittaohjelmat ja niiden analyysi - Karppinen, Tomi (2014)
This master’s thesis is a study of malware and methods and tools used in their analysis in a 32-bit Windows environment. The methods vary from simple observations to deeper static and dynamic analysis in assembly language. In the practical we use these tools and methods to dissect a real world malware sample.